Morphological and functional analysis of saccus vasculosus of mandarin fish ( Siniperca chuatsi ) - Rahma Sakina Said Aly; Jiajie Fang; Keying Li; Xiao Ma; Jiong Gao; Meng Zhang; Xiaowu Chen; Yawei Shen (Journal of Fish Biology, 2026)
The saccus vasculosus (SV) is a specialized periventricular organ found in some species of teleost and elasmobranch fishes, located at the back of the hypothalamus and pituitary gland. However, its function remains incompletely understood. In this study, histological, transmission electron microscopy (TEM) and transcriptomic analyses were employed to investigate the SV of the mandarin fish ( Siniperca chuatsi ) to gain insights into its morphology, gene expression profile and function. Through histological staining techniques, different cell types within the SV can be identified and characterized. The SV is highly folded vascularized neuroepithelium and is deeply connected to blood vessels. TEM studies showed that the capillaries that produced the lumen formed complex narrow channels are linked to the third ventricle of the hypothalamus. The bright neuroepithelium is formed by coronet cells and supporting glial cells, interspersed with liquor‐containing neurons, while the dark contrast is attributed to the presence of heavy elements such as calcium. We identified 28 specific genes in SV, which are most enriched in the purine metabolism pathway, including the genes of pde9al , pde9ac , pde6hl and sgc88el . Gene Ontology biological process analysis for the SV‐specific genes showed that response to osmotic stress was the hub term according to the enrichment maps. Additionally, SV‐specific genes opsin ( opsin8b ), photoreceptor ( pcare1 ) and aquaporin ( aqp4 , aqp9l ) of Siniperca chuatsi may indicate that they play a role as a sensor of season and are involved in osmoregulation. This study, the first on the Siniperca chuatsi , suggests that the SV may have unique physiological functions in teleost fish.